An on-line anomaly identifying method for calibration devices in an automatic verification system for electricity smart meters. (August 2021) - Jiao, Yang; Chen, Qing; Bao, Zhiwei; Pan, Linqiang; Li, Hongbin
Abstract: Calibration devices in an automatic verification system are used to verify the accuracy of electricity smart meters. As time goes by, calibration devices may experience the metering performance degradation, making results of error tests biased. Therefore, it is of great significance to ensure calibration devices have qualified metering performance. Conventionally, their performance could only be manually inspected at regular intervals, while keep unknown during the operation. To address this issue, an on-line anomaly identifying method based on calibration devices' parallel working mode is proposed to check their metering performance in real time. Instead of off-line inspections, a device's metering performance is associated with the corresponding results of error tests, and comparisons among distributions based on results corresponding to different calibration devices would provide evidences to identify the ones having metering performance unqualified without interrupting the verification tasks. In addition, a case study is conducted to prove the validity. Highlights: This method identifies calibration devices with unqualified metering performance. This method is driven by large-scale verification data and could be conducted in real time without interrupting the operation. An adaptive determining strategy is adopted to ensure conclusions' reliability. A case study is conducted to prove the validity.